2004
DOI: 10.1038/sj.gt.3302139
|View full text |Cite
|
Sign up to set email alerts
|

Reduced immunogenicity of DNA vaccine plasmids in mixtures

Abstract: We measured the ability of nine DNA vaccine plasmids encoding candidate malaria vaccine antigens to induce antibodies and interferon-g responses when delivered alone or in a mixture containing all nine plasmids. We further examined the possible immunosuppressive effect of individual plasmids, by assessing a series of mixtures in which each of the nine vaccine plasmids was replaced with a control plasmid. Given alone, each of the vaccine plasmids induced significant antibody titers and, in the four cases for wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
70
2
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 20 publications
(19 reference statements)
7
70
2
1
Order By: Relevance
“…We have also shown in another study this reduction in immune responses to individual proteins when given as a nine-gene mixture to mice. 23 In that study, we demonstrated that the reduction was due to interference among plasmids in a mixture as opposed to a dose effect of the plasmids. 23 Thus, we believe that the reduction in immune responses to individual proteins in the mixture, as opposed to when they were delivered alone in the current studies, was due to interference.…”
Section: Discussionmentioning
confidence: 82%
“…We have also shown in another study this reduction in immune responses to individual proteins when given as a nine-gene mixture to mice. 23 In that study, we demonstrated that the reduction was due to interference among plasmids in a mixture as opposed to a dose effect of the plasmids. 23 Thus, we believe that the reduction in immune responses to individual proteins in the mixture, as opposed to when they were delivered alone in the current studies, was due to interference.…”
Section: Discussionmentioning
confidence: 82%
“…Thus, the mixture of the two individual vaccine candidate components may have resulted in some kind of immunological interference that led to some suppression of the anti-MSP-1 19 IgG response in these animals. This may be due to antigenic competition, a phenomenon known to immunology for over 100 years, and noted in recent immunizations with multiple recombinant malaria antigen plasmids (22). In some cases, a dominant antigen can prevent or reduce the antibody response to another antigen, if the two are administered simultaneously and in the same formulation.…”
Section: Discussionmentioning
confidence: 99%
“…In other instances interference between plasmids has been demonstrated. A nine-plasmid DNA vaccine encoding malaria antigens from the sporozoite, exoerythrocytic and erythrocytic stages of the parasite elicited dramatically reduced immune responses to the component antigens compared with the responses to the plasmids given singly (Sedegah et al, 2004). Furthermore, a plasmid encoding bovine herpesvirus-1 glycoprotein D interfered with plasmids encoding parainfluenzavirus-3 HN or influenza HA, when co-delivered in a mixture, whereas the HN-and HAencoding plasmids did not cause interference (Braun et al, 1998).…”
Section: Discussionmentioning
confidence: 99%